2019
DOI: 10.3390/scipharm87030016
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study: Purple Sweet Potato Extract Seems to Be Superior to Increase the Migration of Impaired Endothelial Progenitor Cells Compared to l-Ascorbic Acid

Abstract: Impairment of the endothelial progenitor cells (EPCs) ability to proliferate and migrate in the patients with coronary heart disease (CHD) is partly caused by oxidative stress. This research evaluates the effect of treatment with Ipomoea batatas L./purple sweet potato (PSP) extract and l-ascorbic acid on the proliferation and migration of impaired EPCs. EPCs were isolated from CHD patient’s peripheral blood. EPCs culture were cultivated and divided into control (untreated), PSP extract treatment (dose 1 and 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Raw images are available as Underlying data 22 . In this study, the use of FITC CD34+ only to confirmed the EPCs are sufficient, as the same EPCs culture method was used in authors previous research 20 , 23 25 . There was also uncertainty about the use of another immunophenotype of EPC as determined by flow cytometry (VEGFR2-PE, vWF-FITC, and CD31-PE), caused by heterogenous types of EPCs 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raw images are available as Underlying data 22 . In this study, the use of FITC CD34+ only to confirmed the EPCs are sufficient, as the same EPCs culture method was used in authors previous research 20 , 23 25 . There was also uncertainty about the use of another immunophenotype of EPC as determined by flow cytometry (VEGFR2-PE, vWF-FITC, and CD31-PE), caused by heterogenous types of EPCs 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…The MTT cell proliferation assay kit (Sigma-Aldrich, St Louis, MO, USA) was used to measure EPCs proliferation as described previously 20 . Treated EPCs were added with MTT reagent and incubated in a 37°C incubator with 5% CO 2 for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it has been shown that Vitamin C treatment alone can improve EPCs migration and proliferation. 25 Vitamin C improves EPCs proliferation and migration via suppression of ROS and pro-inflammatory cytokine (TNF-α in particular) which will reduce p-38 phosphorylation and stimulate…”
Section: Resultsmentioning
confidence: 99%